Protectionism on the rise? New challenges for EU trade policy - Andreas Baur; Lisandra Flach (EconPol Forum, 2023)
We review the EU's trade policy trajectory up to now, situating it within the international context. We then examine new challenges, particularly concerning the resilience of international supply chains and the geopolitical implications of economic interdependencies. Almost 80 percent of all EU imports take place under the most favored nation (MFN) tariff regime. This number illustrates the central importance of the WTO and the multilateral trading system for the EU's external trade. The EU is one of the world leaders in terms of the number of trade agreements: according to the WTO, the EU has 45 trade agreements with 77 countries, which (excluding the EU) account for over 21 per-cent of the world's GDP. However, recent negotiation and ratification processes have often proved lengthy. The event of Brexit and the resulting increase in bureaucratic hurdles illustrate that the extent of economic integration among EU member states is neither self-evident nor irreversible. Instead of aiming for a Europeanization of supply chains and an increase in protectionism, the goal of European trade policy should be the systematic identification and management of critical dependen-cies. The diversification of trade relations is essential in this context
Keywords: 330